10 Ways to waste time on the Web. - Arar, Yardena
Want to idle away a few minutes--or hours? These sites will help you name that tune, test your knowledge of hurricanes, launch a hedgehog, or write a haiku. You'll wonder where the time went.
Keywords: Scrabble (Game); Adtunes.com.; MSN Encarta Quiz; Fail Blog; Kongregate; StumbleUpon; Spirograph; Smalltime industries; Cartoonbank.com.